Negative electrode and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2022063895
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-07
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2042-04-07
AI Technical Summary
【0006】 本開示によれば、ケイ素含有粒子を含む負極であって、サイクル特性の低下が抑制される負極および非水電解質二次電池を提供することができる。
Smart Images

Figure 0007629422000002 
Figure 0007629422000003 
Figure 0007629422000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode, and further to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] Patent Document 1 proposes a negative electrode active material containing silicon-containing particles (SiC) in which silicon domains are dispersed in a carbon matrix. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Special Publication No. 2018-521448 Summary of the Invention [Problem to be solved by the invention]
[0004] A negative electrode containing silicon-containing particles (SiC) with a small silicon domain size is more likely to suppress cracking of SiC due to expansion and contraction accompanying repeated charging and discharging, but carboxymethyl cellulose (CMC) used to bind the SiC surface to the carbon matrix tends to be easily broken during rolling, resulting in a large capacity loss. The object of the present disclosure is to provide a negative electrode containing silicon-containing particles and a nonaqueous electrolyte secondary battery that suppresses deterioration of cycle characteristics. [Means for solving the problem]
[0005] The present disclosure provides the following negative electrode and nonaqueous electrolyte secondary battery. [1] A negative electrode for a non-aqueous electrolyte secondary battery, comprising: A battery comprising a current collector, a first active material layer, and a second active material layer in this order; the first active material layer includes first silicon-containing particles and a first binder; the second active material layer includes second silicon-containing particles and a second binder, The first silicon-containing particle and the second silicon-containing particle contain carbon domains and nano-sized silicon domains dispersed in the carbon domains; The first binder and the second binder contain carboxymethyl cellulose (CMC), a content of carboxymethyl cellulose in the second active material layer is greater than a content of carboxymethyl cellulose in the first active material layer. [2] The negative electrode according to [1], wherein the content of carboxymethyl cellulose in the second active material layer is 0.7 wt% or more and 3 wt% or less, and the content of carboxymethyl cellulose in the first active material layer is 0.5 wt% or more and 1.5 wt% or less. [3] The negative electrode according to [1] or [2], wherein the first silicon-containing particle and the second silicon-containing particle are composed of carbon domains and silicon domains of 50 nm or less, and have an oxygen content of 7 wt % or less. [4] the first active material layer contains first graphite particles; the second active material layer includes second graphite particles; The first graphite particles and the second graphite particles have a BET specific surface area of 3.5 m 2 / g or less, and a particle size distribution (D90-D10) / (D50) is 1.2 or more. [5] The negative electrode according to any one of [1] to [4], wherein the first active material layer and the second active material layer contain single-walled carbon nanotubes. [6] The negative electrode according to any one of [1] to [5], wherein the molecular weight of the carboxymethyl cellulose in the second active material layer is greater than the molecular weight of the carboxymethyl cellulose in the first active material layer. [7] A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of [1] to [6] and an outer casing. [8] The nonaqueous electrolyte secondary battery according to [7], comprising an electrode assembly including the negative electrode, wherein a ratio T / D of a thickness T of the electrode assembly to a distance D between the electrode assembly and an outer casing is 2% or more at a voltage of 3 V or less. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a negative electrode that includes silicon-containing particles and in which deterioration of cycle characteristics is suppressed, and a nonaqueous electrolyte secondary battery. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram showing an example of the configuration of the negative electrode in this embodiment. [Diagram 2] FIG. 2 is a schematic flow chart showing a method for producing a negative electrode. [Diagram 3] FIG. 3 is a schematic diagram showing an example of the configuration of the battery in this embodiment. [Figure 4] FIG. 4 is a schematic diagram showing an example of the configuration of the electrode body in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings, but the present disclosure is not limited to the following embodiments. In all of the drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.
[0009] The negative electrode of the present disclosure will be described with reference to the drawings. The negative electrode 100 shown in FIG. 1 is a negative electrode for a non-aqueous electrolyte secondary battery. The negative electrode 100 includes a current collector 10 and a negative electrode active material layer 20. The negative electrode active material layer 20 includes a first active material layer 30 and a second active material layer 40 laminated in this order from the current collector 10 side. In the negative electrode of the present disclosure, the negative electrode active material layer may be provided on only one side of the current collector, or on both sides.
[0010] The current collector 10 is a conductive sheet. The current collector 10 may include, for example, an aluminum (Al) foil, a copper (Cu) foil, or the like. The current collector 10 may have a thickness of, for example, 5 μm to 50 μm. For example, a coating layer may be formed on the surface of the current collector 10. The coating layer may include, for example, a conductive carbon material, or the like. The coating layer may have a thickness smaller than that of the negative electrode active material layer 20, for example.
[0011] The thickness of the negative electrode active material layer 20 is preferably 100 μm or more and 260 μm or less, more preferably 120 μm or less and 200 μm or more. The packing density of the negative electrode active material layer 20 is preferably 1.2 g / cc or more and 1.7 g / cc or less, more preferably 1.45 g / cc or more and 1.65 g / cc or less. The negative electrode active material layer 20 may have voids. When the negative electrode active material layer 20 has voids, the porosity is preferably 20% or more and 35% or less.
[0012] The first active material layer 30 includes a first silicon-containing particle 31. The second active material layer 40 includes a second silicon-containing particle 41. The first silicon-containing particle 31 and the second silicon-containing particle 41 may be the same or different. The first silicon-containing particle 31 and the second silicon-containing particle 41 are composed of a carbon domain and a nano-sized silicon domain, and preferably composed of a carbon domain and a silicon domain of 50 nm or less. The nano-sized silicon domain is dispersed in a carbon domain matrix. The silicon domain being nano-sized tends to easily suppress cracking of the silicon-containing particle. The size of the silicon domain is measured according to a method described in the Examples section below.
[0013] The first silicon-containing particle 31 and the second silicon-containing particle 41 have an oxygen content of 7 wt% or less. When the oxygen content is in the above range, the capacity tends to be improved. The oxygen content is measured according to the method described in the Examples section below.
[0014] The first silicon-containing particle 31 and the second silicon-containing particle 41 may have voids therein. When voids are present therein, the porosity is preferably 3 volume % or more. The surfaces of the first silicon-containing particle 31 and the second silicon-containing particle 41 may be coated with amorphous carbon.
[0015] The content of the first silicon-containing particles 31 in the first active material layer 30 and the content of the second silicon-containing particles 41 in the second active material layer 40 may be, for example, 1 wt.% or more and 30 wt.% or less, preferably 1 wt.% or more and 20 wt.% or less, and more preferably 1 wt.% or more and 10 wt.% or less.
[0016] The first active material layer 30 further includes a first binder (not shown). The second active material layer 40 further includes a second binder (not shown). The first binder and the second binder include carboxymethyl cellulose (CMC). By including CMC in the first binder and the second binder, the expansion and contraction is large, and the carbon domains tend to easily bind the silicon-containing particles present on the surface. The content of CMC in the second active material layer 40 is higher than the content of CMC in the first active material layer 30. This tends to easily suppress the breakage of the second active material layer, which is on the surface layer side compared to the first active material layer, during rolling, and to easily suppress the decrease in the binding of the active material. The content of CMC in the second active material layer 40 is preferably 0.7 wt% or more and 3 wt% or less. The content of CMC in the first active material layer 30 is preferably 0.5 wt% or more and 1.5 wt% or less.
[0017] The molecular weight of the CMC in the second active material layer 40 is preferably larger than the molecular weight of the CMC in the first active material layer 30, from the viewpoint of suppressing breakage during rolling of the second active material layer 40. The molecular weight of the CMC in the second active material layer 40 may be, for example, 300,000 or more, and the molecular weight of the CMC in the first active material layer 30 may be, for example, 300,000 or less.
[0018] The first binder and the second binder may further contain at least one selected from the group consisting of fluororesins such as polyvinylidene fluoride (PVdF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP), polytetrafluoroethylene (PTFE), polyacrylonitrile, polyimide, polyamide, acrylic resin, polyolefin, polyvinyl alcohol, polyacrylic acid (PAA), polyethylene oxide (PEO), and styrene butadiene rubber (SBR). The total binder content in the first active material layer 30 and the second active material layer 40 may each be, for example, 0.1 wt% or more and 10 wt% or less.
[0019] The first active material layer 30 may further include first graphite particles. The second active material layer 40 may further include second graphite particles. The first silicographite particles and the second graphite particles may be the same or different. The first silicographite particles and the second graphite particles may be artificial graphite. The first silicographite particles and the second graphite particles may have a BET specific surface area of, for example, 3.5 m. 2 / g or less, preferably 0.5m 2 / g or more 3.5m 2 / g or less, more preferably 1m 2 / g or more 2.0m 2 / g or less. When the BET specific surface area is within the above range, the adhesion to the silicon-containing particles tends to be improved. The BET specific surface area is measured by the BET multipoint method.
[0020] The first silicographite particles and the second graphite particles may have any size. The first silicographite particles and the second graphite particles preferably have a particle size distribution (D90-D10) / (D50) of 1.2 or more. In this specification, D10, D50, and D90 respectively represent particle sizes at which the cumulative particle volume from the small particle size side in the volume-based particle size distribution is 10%, 50%, and 90% of the total particle volume. The average particle size of the first silicographite particles and the second graphite particles is preferably 8 μm or more and 30 μm or less. In this specification, the average particle size refers to D50. The particle size distribution and the average particle size can be measured by a laser diffraction / scattering method. The content of graphite particles in the first active material layer 30 and the second active material layer 40 may be, for example, 70 wt% or more and 99 wt% or less, and preferably 80 wt% or more and 99 wt% or less.
[0021] The first active material layer 30 and the second active material layer 40 may further include single-walled carbon nanotubes (hereinafter, also referred to as SWCNTs). The single-walled carbon nanotubes may function as a conductive material. The single-walled carbon nanotubes are preferably carbon nanostructures that form a single cylindrical shape with a single layer of carbon hexagonal mesh planes. The length of the single-walled carbon nanotubes is preferably 0.01 μm or more and 5 μm or less. The diameter of the single-walled carbon nanotubes is preferably 50 nm or less, more preferably 15 nm or less. The first active material layer 30 and the second active material layer 40 contain single-walled carbon nanotubes, which tends to easily suppress the isolation of silicon-containing particles. The content of the single-walled carbon nanotubes in the first active material layer 30 and the second active material layer 40 may be, for example, 0.001 wt% or more and 0.1 wt% or less.
[0022] The method for producing the negative electrode 100 can include slurry preparation (A1), coating (B1), drying (C1), and compression (D1). Fig. 2 is a schematic flow chart showing the method for producing the negative electrode 100. In the present disclosure, first, a first active material layer 30 is formed on a current collector 10, and then a second active material layer 40 can be formed on the first active material layer 30.
[0023] The preparation of the slurry (A1) may include mixing an active material, a binder, and a solvent (water). The amount of the solvent used may be arbitrary. That is, the slurry may have any solids concentration (mass fraction of solids). The slurry may have a solids concentration of, for example, 40% to 80%. Any stirring device, mixer, or disperser may be used for mixing.
[0024] Coating (B1) may include forming a coating film by coating the slurry on the surface of the substrate. In this embodiment, the slurry may be coated on the surface of the substrate by any coating device. For example, a slot die coater, a roll coater, etc. may be used. The coating device may be capable of multi-layer coating.
[0025] Drying (C1) may include heating the coating film to dry it. In this embodiment, any drying device may be used as long as the coating film can be heated. For example, the coating film may be heated by a hot air dryer or the like. The coating film may be heated to evaporate the solvent. This allows the solvent to be substantially removed.
[0026] Compression (D1) may include compressing the dried coating film to form an active material layer. In this embodiment, any compression device may be used. For example, a rolling machine or the like may be used. The dried coating film is compressed to form an active material layer, and the negative electrode 100 is completed. The negative electrode 100 may be cut to a predetermined planar size according to the specifications of the battery. The negative electrode 100 may be cut to have, for example, a strip-like planar shape. The negative electrode 100 may be cut to have, for example, a rectangular planar shape.
[0027] FIG. 3 is a schematic diagram showing an example of a battery in this embodiment. The battery is a non-aqueous electrolyte secondary battery. The battery is preferably a prismatic battery. The battery 200 shown in FIG. 3 includes an exterior body 90. The exterior body 90 houses an electrode body 50 and an electrolyte (not shown). The electrode body 50 is connected to a positive electrode terminal 91 by a positive electrode current collector 81. The electrode body 50 is connected to a negative electrode terminal 92 by a negative electrode current collector 82. The electrode body 50 may be either a wound type or a laminated type. The electrode body 50 is preferably flat. The electrode body 50 includes a negative electrode 100. In FIG. 3, when the distance between the electrode body 50 and the exterior body 90 when viewed from the X direction (length in the Y direction) is D and the thickness of the electrode body 50 (length in the Y direction) is T, it is preferable that the ratio T / D is 2% or more at a voltage of 3V or less. A resin sheet (electrode body holder) may be disposed between the electrode body 50 and the exterior body 90.
[0028] 4 is a schematic diagram showing an example of an electrode body in this embodiment. The electrode body 50 is a wound type. The electrode body 50 includes a positive electrode 20, a separator 70, and a negative electrode 100. That is, the battery 200 includes the negative electrode 100. The positive electrode 60 includes a positive electrode active material layer 62 and a positive electrode current collector 61. The negative electrode 100 includes a negative electrode active material layer 20 and a current collector (negative electrode current collector) 10. EXAMPLES
[0029] The present disclosure will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.
[0030] <Example 1> [Preparation of negative electrode] Negative electrode active material [graphite particles (D10 = 12 μm, D50 = 22 μm, D90 = 40 μm, BET specific surface area = 1.4 m 2[1000g / g], Si-containing particles (SiC) (D50=3μm), conductive material [fibrous carbon (SWCNT, single-layer CNT)], binder [CMC (molecular weight 200,000-300,000, 1% viscosity 3500mPa·s), PAA, SBR] and solvent (water) were kneaded using a stirring granulator to prepare a first slurry. The first slurry had a compounding ratio (mass ratio) of graphite / SiC / SWCNT / CMC / PAA / SBR=94 / 6 / 0.02 / 0.7 / 1 / 1. The prepared first slurry was applied onto a 10μm Cu foil and dried to form a first active material layer. The coating weight on both sides was 107m 2 / g.
[0031] Negative electrode active material [graphite particles (D10 = 12 μm, D50 = 22 μm, D90 = 40 μm, BET specific surface area = 1.4 m 2 [graphite / g], Si-containing particles (SiC) (D50 = 3 μm), conductive material [fibrous carbon (SWCNT, CNT consisting of one layer)], binder [CMC (molecular weight 300,000 to 380,000, 1% viscosity 6500 mPa s), PAA, SBR] and solvent (water) were kneaded using a stirring granulator to prepare a second slurry. The second slurry had a compounding ratio (mass ratio) of graphite / SiC / SWCNT / CMC / PAA / SBR = 94 / 6 / 0.02 / 1.3 / 1 / 1. The prepared second slurry was applied onto the first active material layer and dried to form a second active material layer. The coating weight on both sides was 215 m 2 / g.
[0032] Thereafter, the negative electrode was pressed to a predetermined thickness and processed to a predetermined dimension to obtain a negative electrode (negative electrode plate). The thickness of the negative electrode was 135 μm, and the packing density was 1.60 g / cc. The packing density (g / cc) was calculated by dividing the active material layer by the coating area density Xm 2 / g, thickness Y μm, and is calculated by the formula: packing density Z=X / Y.
[0033] [Preparation of positive electrode] A positive electrode active material [lithium nickel cobalt manganese composite oxide (NCM)], a conductive material [acetylene black (AB)], a binder (PVDF) and a solvent (NMP) were kneaded using a stirring granulator to prepare a positive electrode slurry. The positive electrode slurry was prepared so that the compounding ratio (mass ratio) of the positive electrode active material / conductive material / binder was 100 / 1 / 1. The prepared positive electrode slurry was applied onto a 15 μm Al foil, dried, pressed to a predetermined thickness, and processed to a predetermined dimension to obtain a positive electrode plate.
[0034] [Preparation of non-aqueous electrolyte secondary battery] Leads were attached to the negative and positive electrodes, and the electrodes were laminated with a separator between them to prepare an electrode assembly. The prepared electrode assembly was inserted into an exterior body made of an aluminum laminate sheet, a non-aqueous electrolyte was injected, and the opening of the exterior body was sealed to prepare a test cell (laminate cell). The non-aqueous electrolyte was 1M LiPF 6 The Li salt was used, and a solvent of FEC / EC / EMC / DMC=5 / 15 / 40 / 40 (vol.%) was used. The ratio T / D of the thickness T of the electrode body to the distance D between the electrode body and the outer casing was 2% or more at a voltage of 3V or less.
[0035] [Evaluation of the size of silicon-containing domains] After FIB processing, the negative electrode plate was observed with a STEM (JEM scanning transmission electron microscope manufactured by JEOL Ltd.) and the elements (Si, C) were confirmed by EDX mapping. The silicon-containing domain size was then determined from the shape and contrast obtained in the BF image (bright field image) and HAADF image (high-angle annular dark field image). The results are shown in Table 1.
[0036] [Oxygen content measurement] An oxygen analyzer (Horiba EMGA-830) was used. The amount of oxygen was extracted by the heating and melting method in an inert gas. The sample was melted in Ni / Sn flux, and the O in the sample was analyzed by CO or CO 2 The oxygen content was obtained by converting the mixture into gas and measuring the amount of gas produced. The results are shown in Table 1.
[0037] [Measurement of BET specific surface area] A predetermined weight of the negative electrode active material was inserted into the cell and measured. After the measurement, the BET specific surface area per weight of the active material was calculated. The results are shown in Table 1.
[0038] [Evaluation of cycle maintenance rate] A cycle test was carried out in a 45℃ environment, with CCCV charging (0.33C_4.15V_0.1C cut) followed by CC discharging (0.33C_3V cut) being one cycle, until 150 cycles were reached. The cycle retention rate was calculated as (150cyc discharge capacity) / (1cyc discharge capacity). The results are shown in Table 1.
[0039] <Comparative Example 1 to Comparative Example 3> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the first and second active material layers used silicon-containing particles shown in Table 1 and the CMC contents in the first and second active material layers were set to the ratios shown in Table 1. The results are shown in Table 1.
[0040] [Table 1] [Explanation of symbols]
[0041] 10 current collector, 20 negative electrode active material layer, 30 first active material layer, 31 first silicon-containing particle, 40 second active material layer, 41 second silicon-containing particle, 50 electrode body, 60 positive electrode, 61 positive electrode current collector, 62 positive electrode active material layer, 70 separator, 81 positive electrode current collector, 82 negative electrode current collector, 90 exterior body, 91 positive electrode terminal, 92 negative electrode terminal, 100 negative electrode, 200 battery.
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: A current collector, a first active material layer, and a second active material layer are provided in this order; the first active material layer includes first silicon-containing particles, a first binder, and first graphite particles; the second active material layer includes second silicon-containing particles, a second binder, and second graphite particles; The first silicon-containing particle and the second silicon-containing particle contain carbon domains and nano-sized silicon domains dispersed in the carbon domains; The first binder and the second binder contain carboxymethyl cellulose (CMC), the content of carboxymethyl cellulose in the second active material layer is greater than the content of carboxymethyl cellulose in the first active material layer, the first graphite particles and the second graphite particles have a BET specific surface area of 3.5 m 2 / g or less and a particle size distribution (D90-D10) / (D50) of 1.2 or more; a negative electrode, wherein the first silicon-containing particle and the second silicon-containing particle are composed of a carbon domain and a silicon domain of 50 nm or less, and have an oxygen content of 7 wt % or less.
2. A negative electrode as described in claim 1, wherein the content of carboxymethyl cellulose in the second active material layer is 0.7 wt% or more and 3 wt% or less, and the content of carboxymethyl cellulose in the first active material layer is 0.5 wt% or more and 1.5 wt% or less.
3. The negative electrode according to claim 1 , wherein the first active material layer and the second active material layer contain single-walled carbon nanotubes.
4. 3. The negative electrode according to claim 1, wherein the molecular weight of the carboxymethyl cellulose in the second active material layer is greater than the molecular weight of the carboxymethyl cellulose in the first active material layer.
5. A non-aqueous electrolyte secondary battery comprising the negative electrode according to claim 1 or 2 and an outer casing.
6. 6. The nonaqueous electrolyte secondary battery according to claim 5, comprising an electrode body including the negative electrode, wherein a ratio T / D of a thickness T of the electrode body to a distance D between the electrode body and an outer casing is 2% or more at a voltage of 3 V or less.
Citation Information
Patent Citations
Ultrahigh energy density polymer lithium ion battery negative electrode sheet
CN112310346A
Lithium-ion batteries containing nanofibers
JP2015508937A
Composite powder used for anode of lithium ion battery, method for producing composite powder, and lithium ion battery
JP2018521448A
Composite powder used for anode of lithium ion battery, method for producing composite powder, and lithium ion battery
JP2018521449A
Secondary battery
JP2019179724A